Chemistry - Flowers, Paul, 1962-; Theopold, Klaus, (Klaus Hellmut); Langley, Richard; Robinson, William R.; OpenStax College; BC Open Textbook Project; BCcampus (Openstax College, 2015)
"Published by OpenStax College, Chemistry is designed for the two-semester general chemistry course. For many students, this course provides the foundation to a career in chemistry, while for others, this may be their only college-level science course. As such, this textbook provides an important opportunity for students to learn the core concepts of chemistry and understand how those concepts apply to their lives and the world around them. The text has been developed to meet the scope and sequence of most general chemistry courses. At the same time, the book includes a number of innovative features designed to enhance student learning. A strength of Chemistry is that instructors can customize the book, adapting it to the approach that works best in their classroom."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on May 18, 2016).
Keywords: Chemistry -- Textbooks; Electronic books